PROSPEK PENGEMBANGAN USAHA PERIKANAN TANGKAP DI KOTA BENGKULU (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2015)
Bengkulu city has potential in marine and fisheries sector which has not been managed with maximum. The purpose of this research is to see how the prospects for the development of fishery business in Bengkulu city taking into account the revenue and feasibility of capture fisheries of small fishing boats and paying trawlers boats. This research conducted in Pulau Baai and Pasar Baru. Respondents were selected using census method as many as 24 small fishing boats and 10 payang trawlers boats. Methods analysis using business analytics and business efficiency. This results showed that the fishery business in Bengkulu city has an efficient and feasible to be developed with R/C ratio 2,37 and B/C ratio 1,37 for small fishing boats. For paying trawlers boats obtained R/C ratio 1,52 and B/C ratio 0,52.